Death and the migrant : bodies, borders and care - Gunaratnam, Yasmin (2013)
Using sociological research with dying migrants and care professionals, Death and the Migrant describes the unfolding drama and ordinary predicaments of transnational dying in British Cities. At times of dying, lives are looked back on and memories and losses surface. For migrants and settlers, questions of belonging and 'home' can loom large. The impact of these novel psycho-geographies is also transforming care provision as professionals encounter varied cultural cosmologies and struggle to recognise and alleviate the accumulated pain of social exclusion and injustice. And amidst the churn there are extraordinary stories of generosity and inventiveness that provide new insight into experiences of dispossession and multicultural living, revealing shared human predicaments of how bodies of all kinds survive with frailty, loss and through interdependence. These are matters that bubble up as eschatological questions that ultimately speak to us all. 'Who am I?' 'How did I get here?